98th AES Convention - 25-28.02.1995 - PARIS - Polish AES Section Report; Information about CIB W-51 Acoustics Meeting in Warsaw - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1995)
Audio Engineering Society Conventions became traditional world meetings of all scientist, engineers, industry managers, producers, dealers and even fanciers interested in the domain of sound and vision systems, equipments, facilities, components, hard - and software computer elements etc. Such meetings take place twice a year: Spring Convention in Europe (denoted with consecutive even numbers), and Fall Convention in the USA (denoted with odd ones). The Information Council for Building Research Studies and Documentation is an international organization concerned with studies, research and documentation in the building industry. It unites 70 countries. It has over 500 collective and individual members.